Net Foreign Assets and International Adjustment : The United States, Japan, and Germany - Horne, Jocelyn; Kremers, Jeroen; Masson, Paul. (Washington, D.C. : International Monetary Fund, 1993)
This paper examines external adjustment in the United States, Japan and Germany from the perspective of net foreign asset positions. It asks two questions: What are, in the long run, the determinants of net foreign asset equilibrium? and: What are, in the short run, some of the adjustment mechanisms sustaining that equilibrium? An analysis of post-war data produces two insights. First, using a cointegration approach, the existence of long-run net foreign asset equilibrium can be identified: it is a function of demographic variables and public debt. Second, deviations from long-run equilibrium give rise to feedback through different components of domestic absorption in the three countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet